Using the Knowledge of Post-transcriptional Regulations to Guide Gene Selections for Molecular Breeding in Soybean - Ku, Yee-Shan; Cheung, Ming-Yan; Cheng, Sau-Shan; Nadeem, Muhammad Azhar; Chung, Gyuhwa; Lam, Hon-Ming (Frontiers in Plant Science, 2022)
The omics approaches allow the scientific community to successfully identify genomic regions associated with traits of interest for marker-assisted breeding. Agronomic traits such as seed color, yield, growth habit, and stress tolerance have been the targets for soybean molecular breeding. Genes governing these traits often undergo post-transcriptional modifications, which should be taken into consideration when choosing elite genes for molecular breeding. Post-transcriptional regulations of genes include transcript regulations, protein modifications, and even the regulation of the translational machinery. Transcript regulations involve elements such as microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) for the maintenance of transcript stability or regulation of translation efficiency. Protein modifications involve molecular modifications of target proteins and the alterations of their interacting partners. Regulations of the translational machinery include those on translation factors and the ribosomal protein complex. Post-transcriptional regulations usually involve a set of genes instead of a single gene. Such a property may facilitate molecular breeding. In this review, we will discuss the post-transcriptional modifications of genes related to favorable agronomic traits such as stress tolerance, growth, and nutrient uptake, using examples from soybean as well as other crops. The examples from other crops may guide the selection of genes for marker-assisted breeding in soybean.